Evaluation of hand hygiene practices in three intensive care units - Andre Luiz Silva Alvim; Letícia Cristina Reis; Braulio Roberto Gonçalves Marinho Couto; Carlos Ernesto Ferreira Starling; Raquel Vaz (Universidade de Santa Cruz do Sul, 2019)
Background and objectives: Hand Hygiene (HH) is a simple and effective measure in the fight against Healthcare-associated Infections (HAIs). Despite the effort made by professionals of the Infection Control Service, compliance with practices remains low, generally below 50%. For this reason, this study aimed to evaluate HH practices in three Intensive Care Units of a private hospital in Belo Horizonte, MG, Brazil. Methods: Cross-sectional, descriptive study performed in three ICUs of a private hospital in Belo Horizonte, MG, Brazil. From July 2016 to July 2017, all HH documents of the study hospital were evaluated, totaling 1,100 observations in loco performed by the nurses of the Infection Control Service. Data analysis was performed using descriptive statistics and linear regression using the Pearson correlation coefficient. Results: The rate of adhesion ranged from 27.3 to 88.2%, with an average of 47% (±16.8). Consumption of alcohol preparation and liquid soap obtained, respectively, an average of 32 and 47 ml/patient-day. Pearson's coefficient showed a positive correlation between alcohol consumption and adhesion rate (r=0.49, p=0.01). Conclusion: Healthcare workers still need to be aware of the importance of HH for reducing HAIs.